High shear strength composite anti-seepage liner for high and steep slope of solid waste landfill and preparation method thereof
By using the composite structure of graded sand, polymer modified bentonite and modified sand in GCL materials, the problem of the decrease in shear strength of GCL materials under high load and high moisture content is solved, and the landfill side is significantly improved Structural stability of slope.
Patent Information
- Application Number
- CN202411525466.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The shear strength of existing GCL materials decreases under high load and high moisture content conditions, resulting in problem of structural stability of landfill slopes.
The composite structure of graded sand, polymer modified bentonite and modified sand is adopted to enhance shear strength and structural stability by reducing the amount of flexible materials and introducing hydrophobic sand and reinforcement agents.
The shear strength of the liner material under high normal load is improved, the time of viscosity cohesion is shortened, the shear strength under low load is enhanced, and the structural stability of the landfill slope is significantly improved.
Smart Images

Figure CN119059793B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of anti-seepage materials, and in particular relates to a high shear strength composite anti-seepage liner for high and steep slopes of solid waste landfills and a preparation method thereof. Background Art
[0002] Bentonite waterproof blanket material (GCL) has been widely used in China due to its excellent anti-seepage properties, environmental friendliness and cost-effectiveness, and has gradually replaced the original natural clay anti-seepage structure. However, as its application scenarios and scope of use continue to expand, problems that arise during its application are gradually emerging, among which the most prominent is the structural stability problem in the tailings landfill.
[0003] The current anti-seepage technology treatment plan is an anti-seepage system with HDPE membrane as the main surface layer. HDPE membrane has high requirements for anti-seepage foundation. Generally, natural clay is needed for backfilling and slope adjustment before setting up the anti-seepage liner. In actual engineering, for the sake of structural safety, the slope of the tailings pond is generally controlled at about 1:3. This solution consumes a lot of clay, has a long construction period, high engineering cost, and also greatly reduces the storage capacity of the tailings pond. Increasing the slope gradient will make it difficult for the clay layer and anti-seepage liner used in the anti-seepage system of the tailings landfill to exert their adhesion and have low friction strength. At the same time, the clay layer and anti-seepage liner laid on the steep slope will be subject to greater shear force due to upper settlement, creep, etc., which will cause structural stability to be destroyed and cause the anti-seepage system to fail.
[0004] In the analysis of 15 cases of instability of large landfills in the world in the past 20 years, it was found that only 4 cases were arc sliding failures of garbage bodies inside the landfills, and the remaining 11 cases were structural failures caused by the translation of garbage bodies inside the landfills along the liner system. In all 11 cases, geosynthetics were used in the liner structure. Therefore, the shear performance of geosynthetics such as GCL is one of the important factors affecting the structural stability of anti-seepage projects such as landfills. Studies have shown that under conditions of large loads, the most dangerous sliding failure surface is very likely to appear at the internal interface of GCL, that is, in the filled bentonite. At the same time, through the shear strength experiment of GCL, it was found that the shear strength of GCL gradually decreased with the increase of water content, and the shear strength after complete hydration was much lower than that in the dry state. Through the overall shear test of GCL, it was found that the most dangerous sliding surface of the composite anti-seepage liner material under high normal load is very likely to appear at the internal interface, among which the internal shear strength index of bentonite is very important. At the same time, the actual service process of the anti-seepage liner is a process in which the overlying load and internal water content gradually increase. Therefore, the gradual decrease in shear strength is an inevitable trend, which poses certain safety hazards to the overall structural stability of the project. Summary of the invention
[0005] The purpose of the embodiment of the present invention is to provide a high shear strength composite anti-seepage liner for steep slopes of solid waste landfills and a preparation method. The liner reduces the amount of flexible material used while introducing some hydrophobic sand to enhance structural stability through the application of a "graded sand + high-performance bentonite + modified sand" structure, and enhances the shear strength of the liner material in a saturated state under high normal loads. A reinforcing agent is used to enhance the initial cohesion, and a maximum cohesion of about 80% can be achieved with a water content of about 10%, thereby directionally enhancing the shear strength of the liner material under low normal loads, thereby solving at least one of the technical problems involved in the background technology.
[0006] In order to solve the above-mentioned technical problems, the present invention is achieved as follows:
[0007] The embodiment of the present invention provides a high shear strength composite anti-seepage liner for steep slopes of solid waste landfills, which comprises, by weight, 74-79 parts of graded sand, 5-10 parts of polymer-modified bentonite, 11-18 parts of modified sand and 0.2 parts of a reinforcing agent, wherein the polymer is prepared from acrylamide, acrylic acid and sodium hydroxide, wherein the mass ratio of acrylamide to acrylic acid is 1:12-13, the mass ratio of acrylic acid to sodium hydroxide is 1:0.38-0.42, the reinforcing agent is 1-2 of polyethylene oxide, polyvinyl alcohol, carboxymethyl cellulose and dispersible latex powder, and the modified sand is prepared by the following method:
[0008] Preheat the graded sand with a particle size of 0.075-0.25 mm to 240-260° C., keep it for 1-3 minutes, add one or two of molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mix them evenly, add utrolpine solution and calcium stearate, and crush it after the temperature drops to room temperature to obtain the modified sand.
[0009] Optionally, based on weight, it includes 79 parts of graded sand, 5 parts of polymer-modified bentonite, 16 parts of modified sand and 0.2 parts of reinforcing agent.
[0010] Optionally, based on weight, it includes 76 parts of graded sand, 6 parts of polymer-modified bentonite, 18 parts of modified sand and 0.2 parts of reinforcing agent.
[0011] Optionally, based on weight, it includes 79 parts of graded sand, 6 parts of polymer-modified bentonite, 15 parts of modified sand and 0.2 parts of reinforcing agent.
[0012] Optionally, one or two of phenolic resin, epoxy resin and urea-formaldehyde resin are added to the modified sand in an amount of 0.5%-2% by weight of graded sand with a particle size of 0.075-0.25 mm.
[0013] The present invention also provides a method for preparing the high shear strength composite anti-seepage liner for high and steep slopes of solid waste landfills, comprising the following steps:
[0014] Step 1, weighing sodium bentonite and acrylamide, placing them in a container, adding appropriate amount of water and stirring them evenly to obtain a mud mixture A;
[0015] Step 2, weighing acrylic acid and sodium hydroxide in a container, dissolving the sodium hydroxide in water and fully cooling to room temperature to obtain a sodium hydroxide solution;
[0016] Step 3, mixing the acrylic acid solution with the mud mixture A, and gradually adding the sodium hydroxide solution, during the adding process, always keeping the temperature change of the container less than 10° C. and stirring continuously until the temperature stops rising, to obtain the mud mixture B;
[0017] Step 4, adding potassium persulfate to the mud mixture B, and placing it in an environment of 70-80° C. for 2 hours, and obtaining polymer-modified bentonite after drying and crushing;
[0018] Step 5, preheating the graded sand to 240-260°C, maintaining for 1-3 minutes, adding one or two of the molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mixing them evenly, adding utrolpine solution and calcium stearate, and crushing to obtain modified sand after the temperature is lowered to room temperature; wherein the particle size of the graded sand for preparing the modified sand is 0.075-0.25 mm;
[0019] Step 6: weigh 74-79 parts of graded sand, 5-10 parts of polymer-modified bentonite, 11-18 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water, by weight;
[0020] Step 7, placing all the weighed materials in a mixing container, and stirring them evenly to obtain a graded sand-polymer modified bentonite-modified sand composite material;
[0021] Step eight, preparing a composite anti-seepage liner using graded sand-polymer modified bentonite-modified sand as raw materials.
[0022] Optionally, in step six, 79 parts of graded sand, 5 parts of polymer-modified bentonite, 16 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water are weighed in parts by weight.
[0023] Optionally, in step six, 76 parts of graded sand, 6 parts of polymer-modified bentonite, 18 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water are weighed in parts by weight.
[0024] Optionally, in step six, 79 parts of graded sand, 6 parts of polymer-modified bentonite, 15 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water are weighed in parts by weight.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. In order to solve the problem that the peak shear strength of GCL materials decreases significantly after they are fully hydrated, the present invention adopts the structure of "graded sand + high-performance bentonite + modified sand", reduces the amount of flexible materials, introduces some hydrophobic sand to enhance the structural stability, and enhances the shear strength of the liner material in the saturated state under high normal load.
[0027] 2. The internal interface cohesion of GCL materials is a slow process, and its magnitude increases with the increase of water content. In addition, the water absorption process is relatively long and the complete hydration time is long (generally 1-2 days are required to complete it), which is not conducive to the shear strength of the structure under low load. In this invention, the preferred reinforcing agent is used to enhance the initial cohesion, and the maximum cohesion can reach about 80% at a water content of about 10%, thereby directionally enhancing the shear strength of the cushion material under low normal load.
[0028] 3. In order to solve the problem of low peak saturated shear strength of bentonite in traditional GCL composite materials, the present invention uses a polymer-modified sand composite liner structure to ensure anti-seepage and water-blocking properties while improving engineering economy.
[0029] 4. In order to solve the problem that the shear strength of saturated bentonite in GCL materials is greatly reduced under high load, the present invention takes the internal friction angle of the shear strength index as the research object, and realizes the maximum internal friction angle of 22.07° of the polymer modified sand composite liner under saturated water content (21-23%) by changing the graded sand ratio and introducing quantitative modified hydrophobic sand to enhance the stability of the saturated state. The internal friction angle of hydrated bentonite in traditional GCL is only 10-11°, and the shear strength index τ under saturated state is increased by 96-116%, which can effectively increase the shear strength of the liner material under high upper load under saturated state in use.
[0030] 5. In view of the problem that the shear strength of bentonite in GCL materials is slow to develop under low load, the present invention takes the shear strength index cohesion as the research object. The cohesion of the polymer modified sand composite liner at 10% water content is about 35 kPa, while the cohesion of the polymer modified sand composite liner at saturated water content (21-23%) is about 42-45 kPa. The cohesion is significantly improved and the cohesion develops rapidly with the increase of water content. The internal cohesion c of hydrated bentonite in GCL is only 14-16 kPa. The shear strength index τ at saturated state increases by about 200%, which can effectively increase the shear strength of the liner material under lower upper load at saturated state during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:
[0032] Figure 1 This is a trend diagram of the shear strength of bentonite and composite materials in the GCL provided by the present invention as a function of normal stress. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The embodiment of the present invention provides a high shear strength composite anti-seepage liner for steep slopes of solid waste landfills, which comprises, by weight, 74-79 parts of graded sand, 5-10 parts of polymer-modified bentonite, 11-18 parts of modified sand and 0.2 parts of a reinforcing agent, wherein the polymer is prepared from acrylamide, acrylic acid and sodium hydroxide, wherein the mass ratio of acrylamide to acrylic acid is 1:12-13, the mass ratio of acrylic acid to sodium hydroxide is 1:0.38-0.42, and the reinforcing agent is 1-2 of polyethylene oxide, polyvinyl alcohol, carboxymethyl cellulose and dispersible latex powder.
[0035] The modified sand is prepared by the following method:
[0036] Preheat the graded sand with a particle size of 0.075-0.25 mm to 240-260° C., keep it for 1-3 minutes, add one or two of molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mix them evenly, add utrolpine solution and calcium stearate, and crush it after the temperature drops to room temperature to obtain the modified sand.
[0037] One or two of phenolic resin, epoxy resin and urea-formaldehyde resin are added to the modified sand in an amount of 0.5% to 2% by weight of graded sand with a particle size of 0.075 to 0.25 mm.
[0038] The present invention also provides a method for preparing the high shear strength composite anti-seepage liner for high and steep slopes of solid waste landfills, comprising the following steps:
[0039] Step 1, weighing sodium bentonite and acrylamide, placing them in a container, adding appropriate amount of water and stirring them evenly to obtain a mud mixture A;
[0040] Step 2, weighing acrylic acid and sodium hydroxide in a container, dissolving the sodium hydroxide in water and fully cooling to room temperature to obtain a sodium hydroxide solution;
[0041] Step 3, mixing the acrylic acid solution with the mud mixture A, and gradually adding the sodium hydroxide solution, during the adding process, always keeping the temperature change of the container less than 10° C. and stirring continuously until the temperature stops rising, to obtain the mud mixture B;
[0042] Step 4, adding potassium persulfate to the mud mixture B, and placing it in an environment of 70-80° C. for 2 hours, and obtaining polymer-modified bentonite after drying and crushing;
[0043] Step 5, preheating the graded sand to 240-260°C, maintaining for 1-3 minutes, adding one or two of the molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mixing them evenly, adding utrolpine solution and calcium stearate, and crushing to obtain modified sand after the temperature is lowered to room temperature; wherein the particle size of the graded sand for preparing the modified sand is 0.075-0.25 mm;
[0044] Step 6: weigh 74-79 parts of graded sand, 5-10 parts of polymer-modified bentonite, 11-18 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water, by weight;
[0045] Step 7, placing all the weighed materials in a mixing container, and stirring them evenly to obtain a graded sand-polymer modified bentonite-modified sand composite material;
[0046] Step eight, preparing a composite anti-seepage liner using graded sand-polymer modified bentonite-modified sand as raw materials.
[0047] The following is a detailed description of the method for preparing a high shear strength composite anti-seepage liner for steep slopes of solid waste landfills provided by the present invention with reference to specific embodiments 1-3. Example 1
[0048] Embodiment 1 provides a method for preparing a high shear strength composite anti-seepage liner for a high steep slope of a solid waste landfill, comprising the following steps:
[0049] Step 1, weighing 10 kg of sodium bentonite and 0.1 kg of acrylamide, placing them in a container, adding appropriate amount of water and stirring evenly to obtain a mud mixture A;
[0050] Step 2, weighing 2 kg of acrylic acid and 0.76 kg of sodium hydroxide into a container, dissolving the sodium hydroxide in water and fully cooling to room temperature to obtain a sodium hydroxide solution;
[0051] Step 3, mixing the acrylic acid solution with the mud mixture A, and gradually adding the sodium hydroxide solution, during the adding process, always keeping the temperature change of the container less than 10° C. and stirring continuously until the temperature stops rising, to obtain the mud mixture B;
[0052] Step 4, adding potassium persulfate to the mud mixture B, and keeping it in an environment of 70-80° C. for 2 hours, and obtaining polymer-modified bentonite after drying and crushing;
[0053] Step 5, preheating the graded sand to 240-260°C, maintaining for 1-3 minutes, adding one or two of the molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mixing them evenly, adding utrolpine solution and calcium stearate, and crushing to obtain modified sand after the temperature is lowered to room temperature; wherein the particle size of the graded sand for preparing the modified sand is 0.075-0.25 mm;
[0054] Step 6: weigh 79 parts of graded sand, 5 parts of polymer-modified bentonite, 16 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water, by weight;
[0055] Step 7, placing all the weighed materials in a mixing container, and stirring them evenly to obtain a graded sand-polymer modified bentonite-modified sand composite material;
[0056] Step eight, preparing a composite anti-seepage liner using graded sand-polymer modified bentonite-modified sand as raw materials.
[0057] The shear strength and anti-seepage performance of the composite anti-seepage liner prepared in Example 1 are shown in Table 1.
[0058] Table 1 Shear strength and anti-seepage performance
[0059] Example 2
[0060] Embodiment 2 provides a method for preparing a high shear strength composite anti-seepage liner for a high steep slope of a solid waste landfill, comprising the following steps:
[0061] Step 1, weighing 10 kg of sodium bentonite and 0.1 kg of acrylamide, placing them in a container, adding appropriate amount of water and stirring evenly to obtain a mud mixture A;
[0062] Step 2, weighing 2 kg of acrylic acid and 0.76 kg of sodium hydroxide into a container, dissolving the sodium hydroxide in water and fully cooling to room temperature to obtain a sodium hydroxide solution;
[0063] Step 3, mixing the acrylic acid solution with the mud mixture A, and gradually adding the sodium hydroxide solution, during the adding process, always keeping the temperature change of the container less than 10° C. and stirring continuously until the temperature stops rising, to obtain the mud mixture B;
[0064] Step 4, adding 0.8 kg of potassium persulfate to the mud mixture B, and keeping it in an environment of 70-80° C. for 2 hours, and obtaining polymer-modified bentonite after drying and crushing;
[0065] Step 5, preheating the graded sand to 240-260°C, maintaining for 1-3 minutes, adding one or two of the molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mixing them evenly, adding utrolpine solution and calcium stearate, and crushing to obtain modified sand after the temperature is lowered to room temperature; wherein the particle size of the graded sand for preparing the modified sand is 0.075-0.25 mm;
[0066] Step 6: weigh 76 parts of graded sand, 6 parts of polymer-modified bentonite, 18 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water, by weight;
[0067] Step 7, placing all the weighed materials in a mixing container, and stirring them evenly to obtain a graded sand-polymer modified bentonite-modified sand composite material;
[0068] Step eight, preparing a composite anti-seepage liner using graded sand-polymer modified bentonite-modified sand as raw materials.
[0069] The shear strength and anti-seepage performance of the composite anti-seepage liner prepared in Example 2 are shown in Table 2.
[0070] Table 2 Shear strength and anti-seepage performance
[0071] Example 3
[0072] Example 3 provides a method for preparing a high shear strength composite anti-seepage liner for a high steep slope of a solid waste landfill, comprising the following steps:
[0073] Step 1, weighing 10 kg of sodium bentonite and 0.1 kg of acrylamide, placing them in a container, adding appropriate amount of water and stirring evenly to obtain a mud mixture A;
[0074] Step 2, weighing 2 kg of acrylic acid and 0.76 kg of sodium hydroxide into a container, dissolving the sodium hydroxide in water and fully cooling to room temperature to obtain a sodium hydroxide solution;
[0075] Step 3, mixing the acrylic acid solution with the mud mixture A, and gradually adding the sodium hydroxide solution, during the adding process, always keeping the temperature change of the container less than 10° C. and stirring continuously until the temperature stops rising, to obtain the mud mixture B;
[0076] Step 4, adding 0.8 kg of potassium persulfate to the mud mixture B, and keeping it in an environment of 70-80° C. for 2 hours, and obtaining polymer-modified bentonite after drying and crushing;
[0077] Step 5, preheating the graded sand to 240-260°C, maintaining for 1-3 minutes, adding one or two of the molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mixing them evenly, adding utrolpine solution and calcium stearate, and crushing to obtain modified sand after the temperature is lowered to room temperature; wherein the particle size of the graded sand for preparing the modified sand is 0.075-0.25 mm;
[0078] Step 6: weigh 79 parts of graded sand, 6 parts of polymer-modified bentonite, 15 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water, by weight;
[0079] Step 7, placing all the weighed materials in a mixing container, and stirring them evenly to obtain a graded sand-polymer modified bentonite-modified sand composite material;
[0080] Step eight, preparing a composite anti-seepage liner using graded sand-polymer modified bentonite-modified sand as raw materials.
[0081] The shear strength and anti-seepage performance of the composite anti-seepage liner prepared in Example 3 are shown in Table 3.
[0082] Table 3 Shear strength and anti-seepage performance
[0083]
[0084] Compared with the prior art, the present invention has the following beneficial effects:
[0085] 1. In order to solve the problem that the peak shear strength of GCL materials decreases significantly after they are fully hydrated, the present invention adopts the structure of "graded sand + high-performance bentonite + modified sand", reduces the amount of flexible materials, introduces some hydrophobic sand to enhance the structural stability, and enhances the shear strength of the liner material in the saturated state under high normal load.
[0086] 2. The internal interface cohesion of GCL materials is a slow process, and its magnitude increases with the increase of water content. In addition, the water absorption process is relatively long and the complete hydration time is long (generally 1-2 days are required to complete it), which is not conducive to the shear strength of the structure under low load. In this invention, the preferred reinforcing agent is used to enhance the initial cohesion, and the maximum cohesion can reach about 80% at a water content of about 10%, thereby directionally enhancing the shear strength of the cushion material under low normal load.
[0087] 3. In order to solve the problem of low peak saturated shear strength of bentonite in traditional GCL composite materials, the present invention uses a polymer-modified sand composite liner structure to ensure anti-seepage and water-blocking properties while improving engineering economy.
[0088] 4. Aiming at the problem of significant reduction in shear strength of saturated bentonite in GCL materials under high load, the present invention takes the internal friction angle of shear strength index as the research object, and realizes the internal friction angle of polymer modified sand composite liner under saturated water content state (21-23%) by changing the graded sand ratio and introducing quantitative modified hydrophobic sand to enhance the stability of saturated state. The highest is 22.07°, while the internal friction angle of hydrated bentonite in traditional GCL is only 10-11°. The shear strength index τ under saturated state increases by 96-116%, which can effectively increase the shear strength of the liner material under high upper load under saturated state in use.
[0089] 5. Aiming at the problem that the shear strength of bentonite in GCL material is slow to develop under low load, the present invention takes the shear strength index cohesion as the research object. The cohesion of polymer modified sand composite liner under 10% water content is about 35kPa, while the cohesion of polymer modified sand composite liner under saturated water content (21-23%) is about 42-45 kPa. The cohesion is significantly improved and the cohesion develops rapidly with the increase of water content. The internal cohesion c of hydrated bentonite in GCL is only 14-16 kPa. The shear strength index τ under saturated state increases by about 200%, which can effectively increase the shear strength of the liner material under the action of lower upper load under saturated state during use. The relationship between shear strength, normal stress and cohesion is shown in the following formula:
[0090]
[0091] The shear strength of bentonite and composite materials in GCL varies with normal stress. Figure 1 As shown, Figure 1 GCL1 and GCL2 represent the shear data of two GCL materials.
[0092] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0093] In addition, it should be noted that the scope of the methods and systems in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved. For example, the described methods may be performed in an order different from that described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.
[0094] The embodiments of the present invention are described above, but the present invention is not limited to the above-mentioned specific implementation modes. The above-mentioned specific implementation modes are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, all of which are protected by the present invention.
Claims
1. A high shear strength composite anti-seepage liner for steep slopes of solid waste landfills, characterized in that: The invention comprises 74-79 parts of graded sand, 5-10 parts of polymer-modified bentonite, 11-18 parts of modified sand and 0.2 parts of reinforcing agent by weight. The polymer is prepared from acrylamide, acrylic acid and sodium hydroxide, wherein the mass ratio of acrylamide to acrylic acid is 1:12-13, the mass ratio of acrylic acid to sodium hydroxide is 1:0.38-0.42, the reinforcing agent is 1-2 of polyethylene oxide, polyvinyl alcohol, carboxymethyl cellulose and dispersible latex powder, and the modified sand is prepared by the following method: Preheat the graded sand with a particle size of 0.075-0.25 mm to 240-260° C., keep it for 1-3 minutes, add one or two of molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mix them evenly, add utrolpine solution and calcium stearate, and crush it after the temperature drops to room temperature to obtain the modified sand.
2. The high shear strength composite anti-seepage liner for steep slopes of solid waste landfill according to claim 1, characterized in that: Calculated by weight, it includes 79 parts of graded sand, 5 parts of polymer modified bentonite, 16 parts of modified sand and 0.2 parts of reinforcing agent.
3. The high shear strength composite anti-seepage liner for steep slopes of solid waste landfill according to claim 1, characterized in that: Calculated by weight, it includes 76 parts of graded sand, 6 parts of polymer modified bentonite, 18 parts of modified sand and 0.2 parts of reinforcing agent.
4. The high shear strength composite anti-seepage liner for high and steep slopes of solid waste landfill according to claim 1, characterized in that: Calculated by weight, it includes 79 parts of graded sand, 6 parts of polymer modified bentonite, 15 parts of modified sand and 0.2 parts of reinforcing agent.
5. The high shear strength composite anti-seepage liner for high and steep slopes of solid waste landfill according to claim 1, characterized in that: One or two of phenolic resin, epoxy resin and urea-formaldehyde resin are added to the modified sand in an amount of 0.5% to 2% by weight of graded sand with a particle size of 0.075 to 0.25 mm.
6. A method for preparing a high shear strength composite anti-seepage liner for steep slopes of solid waste landfills as claimed in any one of claims 1 to 5, characterized in that: The steps include: Step 1, weighing sodium bentonite and acrylamide, placing them in a container, adding appropriate amount of water and stirring them evenly to obtain a mud mixture A; Step 2, weighing acrylic acid and sodium hydroxide in a container, dissolving the sodium hydroxide in water and fully cooling to room temperature to obtain a sodium hydroxide solution; Step 3, mixing the acrylic acid solution with the mud mixture A, and gradually adding the sodium hydroxide solution, during the adding process, always keeping the temperature change of the container less than 10° C. and stirring continuously until the temperature stops rising, to obtain the mud mixture B; Step 4, adding potassium persulfate to the mud mixture B, and keeping it in an environment of 70-80° C. for 2 hours, and obtaining polymer-modified bentonite after drying and crushing; Step 5, preheating the graded sand to 240-260°C, maintaining for 1-3 minutes, adding one or two of the molten phenolic resin, epoxy resin and urea-formaldehyde resin into the graded sand and mixing them evenly, adding utrolpine solution and calcium stearate, and crushing to obtain modified sand after the temperature is lowered to room temperature; wherein the particle size of the graded sand for preparing the modified sand is 0.075-0.25 mm; Step 6: weigh 74-79 parts of graded sand, 5-10 parts of polymer-modified bentonite, 11-18 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water, by weight; Step 7, placing all the weighed materials in a mixing container, and stirring them evenly to obtain a graded sand-polymer modified bentonite-modified sand composite material; Step eight, preparing a composite anti-seepage liner using graded sand-polymer modified bentonite-modified sand as raw materials.
7. The method according to claim 6, characterized in that In step six, 79 parts of graded sand, 5 parts of polymer-modified bentonite, 16 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water are weighed in parts by weight.
8. The method according to claim 6, characterized in that In step six, 76 parts of graded sand, 6 parts of polymer-modified bentonite, 18 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water are weighed in parts by weight.
9. The method according to claim 6, characterized in that In step six, 79 parts of graded sand, 6 parts of polymer-modified bentonite, 15 parts of modified sand, 0.2 parts of reinforcing resin and 12 parts of water are weighed in parts by weight.
Citation Information
Patent Citations
Preparation method of anticorrosive coating in natural gas pipeline
CN110358450A
Novel polymer modified sand composite anti-seepage liner and preparation method thereof
CN115259769A